ENGLISH VERB-MARKERS SERVING AS AN ACCURATE PREDICTOR OF ENGLISH PRONUNCIATION: THE CASE OF A VERB- MARKER â-FYâ - Sukrisno, Alim (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
This article deals with English spelling in relation with its segmental and suprasegmental realizations.The reciprocal relationship between English spelling and its pronunciation is mostly arbitrary, and thus unpredictable. However, a closer observation on certain verbal markers, one of which is a verb-marker â-fyâ indicates that to some greater extent itssegmental and suprasegmental realizations are highly predictable.Firstly, English verbs ending in â-fyâmust be segmentally realized as [-faI]. Secondly, English verbs ending in â-fyâ must be stressed on the antepenultimate syllable.A minor exception exists, but a high degree of accuracy is recorded. Owing to the high degree of predictability of its segmental and suprasegmental realizations, the verb-marker â-fyâlends itself to be a predictor of accurate pronunciation. Therefore, teachers as well as students of English as an SL or FL can improve their pronunciation by relying on this observation findings.